2008
DOI: 10.1038/eye.2008.332
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of patient perspectives of clinical teaching in ophthalmology

Abstract: Objective To investigate of the perspectives of ophthalmology patients involved in clinical teaching. Methods In all, 26 patients attending a revision course for postgraduate Membership of the Royal College of Ophthalmologists examination were recruited. Every patient was examined by each of 36 residents who were present on this course making a total of 936 clinical examinations. Patient perspectives on their experience were investigated using a questionnaire. Four domains were investigated: interpersonal aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our review of the literature allowed us to identify a number of studies that explored patients’ participation experiences in hospital-based medical education (Kuan & O’Donnell, 2007 ; Ben Salah et al, 2015 ; Rockey et al, 2020 ) or in primary care and community clinical settings (Prislin et al, 2001 ; Coleman & Murray, 2002 ; Walters et al, 2003 ; Chipp et al, 2004 ; Choudhury et al, 2006 ; Haffling & Hakansson, 2008 ; Heathcote, 2008 ; Ezra et al, 2009 ; Hudson et al, 2010 ; Mol et al, 2011 ; Lucas & Pearson, 2012 ; McLachlan et al, 2012 ; Alao et al, 2021 ; Kjaer et al, 2021 ). These studies highlight that patients overall consider their experience of participating in clinical medical education positive or neutral (Prislin et al, 2001 ; Coleman & Murray, 2002 ; Walters et al, 2003 ; Choudhury et al, 2006 ; Kuan & O’Donnell, 2007 ; Haffling & Hakansson, 2008 ; Ezra et al, 2009 ; Hudson et al, 2010 ; Mol et al, 2011 ; McLachlan et al, 2012 ; Ben Salah et al, 2015 ; Rockey et al, 2020 ; Alao et al, 2021 ). In particular, McLachlan et al’s phenomenological study (2012, p. 969) points out how patients perceive the presence of students in ambulatory consultations “had little potential to do harm, might be of minor benefit to patients, but was assumed to be beneficial to students and therefore to society”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature allowed us to identify a number of studies that explored patients’ participation experiences in hospital-based medical education (Kuan & O’Donnell, 2007 ; Ben Salah et al, 2015 ; Rockey et al, 2020 ) or in primary care and community clinical settings (Prislin et al, 2001 ; Coleman & Murray, 2002 ; Walters et al, 2003 ; Chipp et al, 2004 ; Choudhury et al, 2006 ; Haffling & Hakansson, 2008 ; Heathcote, 2008 ; Ezra et al, 2009 ; Hudson et al, 2010 ; Mol et al, 2011 ; Lucas & Pearson, 2012 ; McLachlan et al, 2012 ; Alao et al, 2021 ; Kjaer et al, 2021 ). These studies highlight that patients overall consider their experience of participating in clinical medical education positive or neutral (Prislin et al, 2001 ; Coleman & Murray, 2002 ; Walters et al, 2003 ; Choudhury et al, 2006 ; Kuan & O’Donnell, 2007 ; Haffling & Hakansson, 2008 ; Ezra et al, 2009 ; Hudson et al, 2010 ; Mol et al, 2011 ; McLachlan et al, 2012 ; Ben Salah et al, 2015 ; Rockey et al, 2020 ; Alao et al, 2021 ). In particular, McLachlan et al’s phenomenological study (2012, p. 969) points out how patients perceive the presence of students in ambulatory consultations “had little potential to do harm, might be of minor benefit to patients, but was assumed to be beneficial to students and therefore to society”.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, three main categories of factors motivating patients to engage in medical education in such clinical contexts emerge: (1) a sense of duty and obligation, interactions with real patients being considered normal and necessary for medical education (Chipp et al, 2004 ; Heathcote, 2008 ; McLachlan et al, 2012 ; Rockey et al, 2020 ), (2) altruistic considerations (i.e., to help future doctors and future patients and to give back to the healthcare system) (Coleman & Murray, 2002 ; Chipp et al, 2004 ; Heathcote, 2008 ; Rockey et a., 2020; Kjaer et al, 2021 ) and (3) the search for personal gain (e.g., better care, improved health knowledge) (Coleman & Murray, 2002 ; Chipp et al, 2004 ; Heathcote, 2008 ; Alao et al, 2021 ; Kjaer et al, 2021 ). The studies also highlight two broad categories of personal gains that patients consider they derive from their participation experience: (1) pragmatic, utility-maximizing gains (e.g., perceived improvement in quality of care in terms of medical expertise, consultation time and patient education, increased clinical knowledge about their health condition) (Prislin et al, 2001 ; Ezra et al, 2009 ; Mol et al, 2011 ; Lucas & Pearson, 2012 ; McLachlan et al, 2012 ; Alao et al, 2021 ) and (2) therapeutic gains (e.g., personal satisfaction; enhanced self-esteem and empowerment, sense of meaning and usefulness, enhanced happiness and well-being through the care pathway, new insights into their illness and care experience) (Walters et al, 2003 ; Haffling & Hakansson, 2008 ; Ezra et al, 2009 ; Mol et al, 2011 ; Lucas & Pearson, 2012 ; Rockey et al, 2020 ; Kjaer et al, 2021 ). Very few studies address the disadvantages identified by patients (Walters et al, 2003 ; Heathcote, 2008 ).…”
Section: Introductionmentioning
confidence: 99%